Imagining and appreciating "the long eye of history": race, form and representation in Drum magazine's serialisation of wild conquest. (2nd January 2019) - Peterson, Bhekizizwe
ABSTRACT: Newspapers and magazines in South Africa are acknowledged as having played a significant role in the fostering of literary journalism and criticism amongst black writers. Drum is commended for inaugurating the flourishing of the short-story genre. The launch of Drum in 1951 was preceded by the departure of Abrahams from South Africa to England in September 1939. Yet Drum and Abrahams – through his novel Wild Conquest, travelogue and autobiography Return to Goli and Tell Freedom – initiated an important conversation on the limits and possibilities of the synergies between the different platforms and genres in print culture and the extent to which they can capture and navigate the divergent aesthetic and socio-political imperatives that informed the magazine, writers and readers. This paper is an examination of Drum 's promotion of reading and writing amongst black South Africans from 1951–1960 as reflected in its intermittent forays in the serialisation of novels. It uses the magazine's interpellation of Peter Abrahams and his work during 1951–1960 as a case-study into the intricate web and tensions of context, form and theme as well as the genealogies of writing and hermeneutics in black South African literature.